Assessment of Antitick and Repellent Activity of Azadirachta indica Oil against Adults and Larvae Stages of Rhipicephalus microplus - Mukesh Shakya; Mamta Singh; Kalpana Gautam; Sunita Jamra; Vivek Agrawal; A. K. Jayraw; G. P. Jatav; S. K. Gupta; Sachin Kumar (Psyche: A Journal of Entomology)
Ticks are blood-sucking parasites and occur all over the world, especially in humid and subhumid nations such as India. They are very important vectors of many economically important livestock diseases, such as Anaplasma spp., Babesia spp., and Theileria spp. Ticks were collected from organized and unorganized cattle farms situated in and around Mhow. The initially collected samples of ticks (≤200) were washed in tap water and identified as Rhipicephalus microplus. The study was carried out from June 2021 to May 2022. Ticks were treated with 0.625, 1.25, 2.50, 5, and 10% oil of Azadirachta indica in both the adult immersion test and larval immersion test. All the concentrations were prepared with absolute ethanol. In the present study, fipronil was used as a positive control using various concentrations (x/8, x/4, x/2, x, and 2x) and was prepared in distilled water. The LC50 values against fipronil were observed as 1.03 and 1.12 ppm for adults and larvae, respectively. Results of the study showed that the oil of Azadirachta indica was responsible for the mortality of adults (LC50 = 2.70%) and larval stages (LC50 = 1.27%) at all the concentrations used. Furthermore, it was observed that this oil was also responsible for the inhibition of oviposition and had excellent repellent activity at 10% concentration. Based on the study, we can conclude that the oil of A. indica can be used in an integrated tick management system to reduce the tick burden on animals.